Learning Strategies of Two Thai Undergraduate Students - Ista Maharsi (Universitas Muhammadiyah Prof. DR. HAMKA, 2019)
Language learning strategies are important for students to help develop their language competences and succeed academically. This paper is aimed to identify the learning strategies used by two Thai university students taking English language training program. The two female students speak Thai language as their mother tongue, Bahasa Indonesia and English as their second/foreign languages. Data were collected from interviews, observations, and documents. Results of this study reveal that those two Thai students employ two learning strategies—compensation strategies (getting help, using mime or gesture, avoiding communication partially or totally, and selecting topic) and metacognitive strategies (overviewing and linking with already known materials, identifying the purpose of a language task, seeking practice opportunities, and self-evaluating). Several emergent findings are paying attention to classmates and memorizing strategy. Difficulties in finding speaking partners as well as the feeling of reserved and shy are indicated as speaking problems. To help them with such problems, Google Translate is also perceived as beneficial to translate unknown words and expressions. Keywords: learning strategies, EFL students, qualitative inquiries